O surfe nas ondas da mídia : um estudo de Fluir nos anos 1980 - Soares, Rafael Fortes (2010)
The research which originated this thesis aimed to investigate Fluir magazine between 1983 and 1988. The main question was to discuss the role played by that publication as a mediator of surfing experience for its readers. The subject is looked at though the notion of niche media, whose values and way of functioning have clear differences in relation to hegemonic journalism. Through the concepts of niche media and subcultures, this thesis seeks to put in perspective the categories (specialyzed journalism and segmented journalism) commonly used to analyse this kind of subject as a part of traditional journalism. Surfing is understood as a media subculture, which helps explore its cultural dimension, more precisely, the role played by that publication in constructing and spreading out the sport and its values (including social class). This thesis analyses the role Fluir magazine played in this development process and in the strong expansion of the surfing market. The methodology combines content analysis of text and image (specially photographs), which looks over both journalism and advertising. All editions published between 1983 and 1988 available on the Periodics section of Brazilian National Library were investigated. In a less sistematic way, films, other publications on surfing and extreme sports, books and internet websites were also observed. The time range covers a period in which surfing suffered intense transformations and was definitely consolidated as a professional sport in Brazil. This study has found that the growing of three elements surf market, surfing as a sport and Fluir are closely bonded: each process feeds and strenghtens the others. In this sense, the media has a key role in giving visibility to the agents involved, constructing representatios on aspects such as the Brazilian surfer s quality, company roles, travels, competitions, sponsorship and gender. This is done in order to present surfing as a healthy and positive sport, fighting against a series of stigmas that covers itself and its adepts.